Retranslating Joyce for the 21st century - Wawrzycka, Jolanta W.; Mihálycsa, Erika (European Joyce studies, 2020)
"The essays in Retranslating Joyce for the 21st-Century straddle the disciplines of Joyce studies, translation studies, and translation theory. The newest scholarly developments in these fields are well reflected in recent retranslations of Joyce's works into Italian, Portuguese, French, Dutch, Turkish, German, South Slavic, and many other languages. Joyce critics and Joyce translators offer multi-angled critical attention to the issues of translation and retranslation, enhanced by their diverse linguistic and cultural backgrounds and innovative methodologies. Because retranslations of Joyce have also exerted significant influence on target language cultures, students and readers of Joyce and, more broadly, of modernist and world literature, will find this book highly relevant to their appreciation of literature in translation"--